Addition to the species composition of myxomycetes of Shatskyi National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
In August 21–23, 2018, 32 species of myxomycetes from 25 genera, 10 families, 6 orders, and 2 subclasses of the class Myxomycetes were found on the territory of the Shatskyi National Nature Park. Among species revealed this study, only 9 were found during the previous survey of this reservation area in 2004. In the taxonomic spectrum of myxomycetes of the Shatskyi NNP, calculated on the basis of findings of both 2004 and 2018, the subclass Columellomycetidae is represented by 36 species (58.1%), while the Lucisporomycetidae includes 26 species (41.9%). Representatives of orders Stemonitidales (17; 27.4%) and Physarales (16; 25.8%) and families Physaraceae (13 species, 21%), Amaurochaetaceae (10; 16.1%), Trichiaceae (9; 14.5%), Stemonitidaceae and Cribrariaceae (7; 11.3% each) appear to be most common in the National Park. Among genera, the most species-rich are Cribraria Pers., Stemonitis Roth, and Physarum Pers. 17 species of myxomycetes (50.0%) formed fruiting bodies on the dead wood, 15 species (44.1%) were collected on the bark of living trees; species diversity on the leaf litter (7; 20.6%) and the branch litter (6, 17, 7%) was significantly lower. Only one species, Symphytocarpus trechispora (Berk. ex Torrend) Nann.-Bremek., was found on live grassy angiosperms and bryophytes, on the Sphagnum bog. Among the substrate-forming plants, Pinus sylvestris L. (25 species; 73.5%), Alnus glutinosa (L.) Gaertn. (10; 29.4%) and Betula pendula Roth (7; 20.6%) appeared to be the most favorable for the myxomycete fructification under the conditions of the Shatskyi NPP; significantly fewer species were found on substrates formed by Populus cf. alba L. (3; 8.8%), P. tremula L. (2; 5.9%), Quercus robur L. (2; 5.9%), Pyrus communis L. (1, 3%) and Betula pubescens Ehrh. (1, 3%). Interestingly, in the eastern part of Ukraine, Q. robur and P. tremula seem to be much more favorable for myxomycetes. Among the discovered species, 23 are new to the National Park and 18 are new to Western Polissia (forest belt in the North of Ukraine). Licea hydrargyra Nann.-Bremek., T.N. Lakh. & R.K. Chopra, L. pumila G.W. Martin & R.M. Allen and Symphytocarpus trechispora have been recorded in Ukraine for the first time, and the first two species are also new for the Eastern Europe. The discovering of these species became possible due to the moist chamber method, which was never used before in studies of myxomycetes in Western Polissia region.
Keywords: moist chamber method, substrate preferences, new species for Ukraine.